2009
DOI: 10.4103/0378-6323.57721
|View full text |Cite
|
Sign up to set email alerts
|

Autoimplantation therapy for multiple warts

Abstract: This study demonstrates that homologous autoimplantation could be an effective, simple modality of treatment for multiple warts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 4 publications
4
52
4
Order By: Relevance
“…A complete clearance of warts was observed in 34.69% patients in our study. Whereas, Shivakumar et al, Srivastava et al and Nischal et al observed a complete clearance of warts in 73.3%, 66.03% and 74.1% respectively 2,6,8 . However, a 67.74% reduction in the mean number of warts and a 48.71% reduction in the mean size of warts was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A complete clearance of warts was observed in 34.69% patients in our study. Whereas, Shivakumar et al, Srivastava et al and Nischal et al observed a complete clearance of warts in 73.3%, 66.03% and 74.1% respectively 2,6,8 . However, a 67.74% reduction in the mean number of warts and a 48.71% reduction in the mean size of warts was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…No treatment till date has been validated to be 100% effective in clearing viral warts. Hence, multiple treatment modalities have been tried with an average of 60-70% clearance of warts in 3 months time 6 . The ultimate wart treatment would resolve all or a great percentage of warts, be painless, need only one or a part of a wart treated, call for one to three treatments, create no scarring, offer HPV immunity for a lifetime and be available to all patients 9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations